ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA DAN PROFITABILITAS EFFICIENCY ANALYSIS OF THE USE OF WORKING CAPITAL AND PROFITABILITY - Marantika, Abshor (Jurnal Manajemen dan Keuangan, 2012)
Working capital plays a very important for any coroporate which needs capital and good working capital management to ensure continuity of the company, which means how well the profitability ratios illustrate the ability of the company generate profits. The purpose of this study is to see how the effect of working capital on profitability in LQ45 companies listed on the Indonesia Stock-year period from 2007 to 2010, using secondary data that the financial statements of 17 companies in the LQ45 index listed in the Indonesia Stock Exchange. Research Method this research is associative. While the study population was LQ45 companys financial statements listed in the Indonesia Stock Exchange (BEI), and the sample in this study are the financial statements of 17 companies listed on the Stock Exchange LQ45 year 2007-2010. In the data analysis technique, there is anecdotal evidence that there is the effect of variable X (working capital) to variable Y (profitability). Authors using simple linear regression analysis to examine the effect of working capital and a ROE of 17 companies the period 2007-20010. The statistical result obtained from a simple regression analysis there was no significant effect of the variable X (working capital) to variable Y (profitability / return on equity). This is due to sig (0.065)> alpha (0.05) that accept and reject Ho Ha and on t count (3.734)> t table (2.92) then accept Ho and reject Ha.Keywords : Working Capital, Profitability Ratios